(untitled) (Homiletic, 2018)
The problem of in-class sermon feedback has vexed the teaching and learning of preaching for some time. For too long, however, the problem has been understood in more or less personal terms insofar as it tries to facilitate an environment where task mastery becomes psychologically feasible for students in a stressful feedback situation. This article argues that the problem of sermon feedback is actually more complex in that it is also tied to privilege, power dynamics, and the multiple identities of the pluralistic classroom and cultural identities in churches. The use of facework theory in communication studies offers an alternative by placing task mastery in relation to the tending to identities in the room. Here the work of Jeff Kerssen-Griep et al. posits a compelling vision for dealing with an analogous face-threatening situation of speech feedback in the college classroom that includes both positive (belonging, competency) and negative (autonomy) facework and thus locates task mastery in relation to tending to identities in a more self-reflective manner. In the process, a more mentoring-type relation between teacher and student is envisioned, one that might even build on Dale Andrews’ notion of apprenticeship in preaching education. The article concludes with homiletical-theological reflections about the relationship of face/Face and promise in reflecting on gospel in the task of teaching and learning preaching.